Pemeriksaan Setempat (Descente) Terhadap Anak dalam Sengketa Hak Asuh Anak: Analisis Putusan Hakim di Lingkungan Pengadilan Agama di Indonesia - Nur Syamsiah; Erina Pane; Linda Firdawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Descente or site visit are usually carried out on material cases, such as inheritance cases, joint property, sharia economics and so on, with the aim of avoiding difficulties in carrying out the execution of decisions at a later date. However, in several decisions, site visit were also found in cases other than material things, including in disputes over child custody or hadhanah by examining Decision Number 1063/Pdt.G/2022/PA.Tgm, Decision Number 627/Pdt.G/2023/ PA.Prw and Decision Number 585/Pdt.G/2020/PA.Ppg. This research is normative legal research or library research with a conceptual approach which examines primary data from several judicial decisions in Indonesia such as the Tanggamus Religious Court, the Pringsewu Religious Court and the Pasir Pangaraian Religious Court. The results of the research show that the implementation of site visit of children is the same as site visit of material cases and there are two reasons why the panel of judges conducts site visit of site visit of these cases, namely: directly ensuring the objective condition of the child and the child's growth and development and also ensuring environmental conditions. around the child in order to realize the best interests of the child. Site visit of children, apart from fulfilling the best interests of the child, also fulfills the objectives of Islamic law in maqāṣid asy-syarīah, namely hifz al-nafs or soul.